THE EFFECT OF INFORMATION SHARING, DECISION SYNCHRONIZATION, AND INCENTIVE ALLIGNMENT ON INTER-ORGANIZATIONAL TRUST - Zainuddin Latuconsina (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
This research aims to analyze the effect of information sharing, decision synchronization, and incentive alignment on inter-organizational trust. Data analysis technique uses Partial Least Square. Respondents in this research are general managers, owners, board of directors, and administrative staffs of the companies, especially those related to supplier-retailer or retailer-supplier relationships in Ambon City, with a total of 51 people. The results show that information sharing has an effect on inter-organizational trust. Decision synchronization has no effect on inter-organizational trust. Incentive alignment also has an effect on inter-organizational trust.